Sosialisasi Pendampingan Implementasi Program Kebijakan PAUD-HI di TK Pocut Meuligoe Samalanga Kabupaten Bireuen - Karuni Humairah Arta; Arfriani Maifizar; Ikhwan Rahmatika Latif; Ilham Mirza Saputra; Najamudin Najamudin; Afrizal Tjoetra; Khairan Khairan; Chairul Iqbal Aziz; Reza Fahlevi (Universitas Teuku Umar, 2026)
Holistic Integrative Early Childhood Education (PAUD-HI) is a strategic approach to fulfilling the essential needs of early childhood, including education, health, nutrition, care, protection, and welfare. This community service activity aimed to provide socialization and mentoring on the implementation of the PAUD-HI program at TK Pocut Meuligoe Samalanga, Samalanga District, Bireuen Regency. The activity employed a participatory approach through material presentations, interactive discussions, and question-and-answer sessions involving school principals, teachers, and school committee members. The materials delivered included PAUD-HI policies based on Bireuen Regent Regulation Number 4 of 2020, priority PAUD-HI programs, and PAUD management. The results indicate that the participant targets were successfully achieved, the materials were well understood, and participants showed high enthusiasm throughout the activity. This program is expected to enhance stakeholders’ understanding of PAUD-HI implementation and contribute to improving the quality of early childhood education services in a sustainable manner.